2013
DOI: 10.1016/j.jtcvs.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic outcomes of radial artery versus saphenous vein in coronary artery bypass graft surgery: A meta-analysis of randomized controlled trials

Abstract: While acknowledging the limitations of heterogeneous surgical techniques, results from the present meta-analysis suggest potential superiority of the RA compared with the SV at midterm angiographic follow-up. However, the increased incidence of string sign associated with the RA is of potential clinical concern. Further research should be directed at correlating angiographic findings of string sign and graft failure to clinical symptoms and major adverse cardiac and cerebrovascular events at long-term follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 35 publications
2
67
0
3
Order By: Relevance
“…49) Recently, Cao and colleagues compared angiographic outcomes in 859 RA and 849 SVG from 5 RCTs at one-and four-years. 50) At one-year there was no significant difference in the occlusion rate between the RA and SVG (9.1% versus 12.7%, OR 0.71) but a far higher incidence of "string sign" in the RA grafts (7.4% versus 1.0%, OR 7.97). At 4 years RA occlusion was reduced significantly (2.7% versus 14.7%, OR 0.17) with no significant difference in string sign (2.7% versus 0%, OR 3.55).…”
Section: )mentioning
confidence: 87%
“…49) Recently, Cao and colleagues compared angiographic outcomes in 859 RA and 849 SVG from 5 RCTs at one-and four-years. 50) At one-year there was no significant difference in the occlusion rate between the RA and SVG (9.1% versus 12.7%, OR 0.71) but a far higher incidence of "string sign" in the RA grafts (7.4% versus 1.0%, OR 7.97). At 4 years RA occlusion was reduced significantly (2.7% versus 14.7%, OR 0.17) with no significant difference in string sign (2.7% versus 0%, OR 3.55).…”
Section: )mentioning
confidence: 87%
“…A meta-analysis of five studies showed no remarkable superiority of radial artery grafts over SVGs, due to string phenomenon that occurs with the former. 77) In contrast, the recent randomized controlled Radial Artery Versus Saphenous Vein Patency (RSVP) trial found a higher patency rate with radial arteries when compared to SVGs over 5 years of follow-up. 74) Such variability of the results is of course thought to be dependent on the level of expertise of the surgeon harvesting the graft.…”
Section: Radial Arterymentioning
confidence: 94%
“…A number of studies have investigated the patency rate of radial artery grafts, 65,74,76,77) and the results vary. A meta-analysis of five studies showed no remarkable superiority of radial artery grafts over SVGs, due to string phenomenon that occurs with the former.…”
Section: Radial Arterymentioning
confidence: 99%
See 1 more Smart Citation
“…However, autologous bypass material is sparse, especially in re-do coronary artery bypass grafting cases. Meta-analyses suggest superiority of the radial artery over the saphenous vein concerning patency [2,3]. RA patency rates range from 83% to 93% at one to seven years after operation [4].…”
Section: Introductionmentioning
confidence: 99%